Side Effects of Using Disinfectants to Fight COVID-19 - Yari, Saeed; Moshammer, Hanns; Fallah Asadi, Ayda; Mosavi jarrahi, Alireza (Asian Pacific Journal of Environment and Cancer, 2020)
Coronavirus refers to a group of widespread viruses. The name refers to the specific morphology of these viruses because their spikes look like a crown under an electron microscope. Coronavirus disease (COVID-19) is an infectious disease caused by a newly discovered crown-shaped virus. Human-to-human transmission of the coronavirus is through coughing, sneezing, discharge from the nose and mouth. The virus can be transmitted from 1 to 2 meters through coughing or sneezing. Another way of transmission is by hand contact with the environment and virus-infected surfaces. Various substances are used to disinfect the body and surfaces. However, improper and unsafe use of these disinfectants can lead to other toxic effects in people that can be far more dangerous than the virus itself.